1996
DOI: 10.1016/s0306-4530(96)00012-1
|View full text |Cite
|
Sign up to set email alerts
|

A nose-brain pathway for psychotropic peptides: evidence from a brain evoked potential study with cholecystokinin

Abstract: The access of substances to the brain is of particular relevance for the etiology and treatment of psychiatric and neurologic diseases. This study provides functional evidence for a direct access of peptides to the human brain after intranasal administration. Effects were compared of intranasal (IN, 10 micrograms) and intravenous (i.v., 0.25 and 2.5 micrograms) administered cholecystokinin-8 (CCK) on the auditory event related potential (AERP) in 20 healthy subjects. Also, plasma concentration of cortisol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…Furthermore, plasma concentrations of vasopressin during task performance were enhanced more after the intravenous administration of AVP than after nasal administration. Similar results were obtained by the same group after nasal and intravenous administration of cholecystokinin-8 (Pietrowsky et al 1996b) and performance of an auditory attention task (oddball task) in 20 volunteers in a double blind cross-over study recording the auditory event-related brain potentials. Further studies confirmed the results (Pietrowsky et al 2001).…”
Section: Human Studiessupporting
confidence: 81%
“…Furthermore, plasma concentrations of vasopressin during task performance were enhanced more after the intravenous administration of AVP than after nasal administration. Similar results were obtained by the same group after nasal and intravenous administration of cholecystokinin-8 (Pietrowsky et al 1996b) and performance of an auditory attention task (oddball task) in 20 volunteers in a double blind cross-over study recording the auditory event-related brain potentials. Further studies confirmed the results (Pietrowsky et al 2001).…”
Section: Human Studiessupporting
confidence: 81%
“…In more recent studies, direct transport of the peptides arginine-vasopressin and cholecystokinin-8 from the nose to the brain has been reported in humans, providing encouraging evidence that use of drug delivery via the olfactory pathway may be possible in patients with a variety of brain disorders (22,23).…”
Section: Discussionmentioning
confidence: 95%
“…A variety of substances, including the antibiotic cephalexin (24), the steroid hormone progesterone (16), the peptides vasopressin (22) and cholecystokinin (23) and the protein horseradish peroxidase (HRP) (2), have all been proposed to undergo extraneuronal transport from the nasal cavity to the CNS. For instance, following unilateral intranasal administration, HRP (40 kDa) has been found within 45-90 min in intercellular openings of the olfactory epithelium as well as on the pial surface and nerve fiber layer of the olfactory bulb bilaterally in both rats and monkeys (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent neuropharmacological research has shown that neuropeptides gain access to the human brain after intranasal administration [18, 41,66,129], providing a useful method for studying the central nervous effects of OT and AVP in humans [68]. In particular, a potential clinical use is dependent on a more direct and secure pathway to the human brain.…”
Section: Methodological Approaches In Human Neuropeptide Researchmentioning
confidence: 99%